PENGARUH SOLVABILITAS TERHADAP PROFITABILITAS DI NATHAN’S FAMOUS INC - Eben Ezer Pakpahan (Jurnal Administrasi Bisnis, 2017)
This study sought to open to the public about the relationship between the solvency of profitability. Every company is trying to manage short-term funds and long-term to finance its operations and meet its short-term liabilities and long term liabilities. The Results showed the ratio of a company's ability to obtain profit (return on assets, return on equity and return on investment) in 2010 increased and decreased in 2011 and in 2012 the company managed to make corrections to its ability to make a profit. The solvency ratio increased from 2009 to 2012.Financing of the company be dominated by debt, especially short term debt.Even thougt the corporate cash flow on a daily basis so that it can finance its operations every day, but the company must be careful with the payment of maturing debt and interest costs. Earnings ratios (profitability) coefficient of variation is the lowest one is the return on assets, followed by return on equity and return on investment. Coefficient of variation of the lowest to the solvency ratio is the debt ratio, followed by a debt equity ratio and capitalization ratio. Debt ratio has a significant relationship with return on assets, return on equity and return investment.The correlation between debt ratio with return on assets is very strong , as well as a very large debt ratios as a determinant of return on assets but the increase in the debt ratio will cause a decrease in return on assets and return on investment, return on equity except is increasing.Debt to equity ratio has a significant association with the return on assets, return on equity and return on investment. Increased debt equity ratio will cause increasing return on equity, but causes a decrease in return on assets and return on investment.